Controlled switching of phase-change materials by evanescent-field coupling in integrated photonics - Rios, C; Stegmaier, M; Cheng, Z; Youngblood, N; Wright, C; Pernice, W; Bhaskaran, H (Optical Society of America, 2018)
Fully controllable phase-change materials embedded in integrated photonic circuits are a promising platform for on-chip reconfigurable devices. Successful experimental demonstrations have thus far enabled non-volatile multilevel memories and switches, optical synapses, and on-chip photonic computing. However, the origin and mechanism behind the phase switching has not been described in detail. In this paper, we study qualitatively the evanescent field coupling between Ge2Sb2Te5 and the confined mode within a Si3N4 rib waveguide. To do so, we carry out simulations and compare to experimental results to reveal the switching dynamics that drives the precise control during amorphization and crystallization. Furthermore, we study the unique deterministic control of intermediate states for multilevel applications. By better understanding of the physics behind the phase switching, optimized parameters for faster and more energy efficient devices are proposed. This, in turn, offers a better perspective on the applicability of phase-change materials in multilevel reconfigurable optics and novel computing architectures.